Hypothalamic Energy Regulatory Peptides in Chronic Kidney Disease. Issue 5 (21st March 2019) - Korucu, Berfu; Erten, Yasemin T; Yeter, Haci H; Altinova, Alev; Pasaoglu, Ozge T; Pasaoglu, Hatice; Sindel, Mahmut S; Arinsoy, Selim T; Yetkin, Ilhan
Abstract: Loss of appetite affects one‐third of patients with CKD and is the leading cause of malnutrition in this population. Orexigenic Agouti‐related peptide (AgRP) with neuropeptide‐Y (NPY) and anorexigenic melanocyte‐stimulating hormone‐α (MSH‐α) with cocaine‐ and amphetamine‐regulated transcript (CART) are known to regulate appetite. In this study, we aimed to evaluate the levels of these peptides in CKD patients compared to healthy subjects and demonstrate the effects of dialysis treatment and erythropoiesis‐stimulating agent (ESA) therapy. The cross‐sectional study is composed of consecutive inclusion of 20 healthy individuals, 20 predialysis CKD patients, 20 HD, and 20 peritoneal dialysis (PD) patients. Exclusion criteria were an active infection, history of malignancy, hypo‐ or hyperthyroidism, and diabetes. Patients on dialysis had targeted Kt/Vs. Demographic features and BMIs of the four groups were similar. Levels of AgRP, NPY, AMSH, and CART were significantly different between groups. Nondialysis CKD patients had significantly lower hypothalamic hormones compared to healthy individuals, HD and PD patients ( P = 0.02, P = 0.03, and P = 0.07 for AgRP; P = 0.02, P  = 0.01, and P  = 0.09 for NPY; P  = 0.02, P  = 0.02, and P = 0.03 for AMSH; P  = 0.02, P = 0.005, and P = 0.030 for CART). Dialysis patients with or without ESA treatment had similar hormone levels ( P  = 0.13 for AgRP; P  = 0.11 for NPY; P  = 0.23 for AMSH, and P  = 019 for CART). Predialysis CKD patients have lower orexigenic and presumably indirectly lower anorexigenic peptides compared to healthy subjects and dialysis patients. ESA treatment does not affect these hypothalamic peptides in dialysis patients.